Absolute lymphocyte count and human adenovirus–specific T‐cell immune restoration of human adenovirus infection after kidney transplantation. Issue 8 (3rd April 2019) - Bruminhent, Jackrapong; Apiwattanakul, Nopporn; Hongeng, Suradej; Kantachuvesiri, Surasak; Watcharananan, Siriorn P.
Abstract: Introduction: Human adenovirus (HAdV) infection can cause substantial morbidity in kidney transplant (KT) recipients. Cell‐mediated immunity plays an important role in controlling HAdV infection after KT. Methods: We prospectively (January 2015 to June 2018) investigated the absolute lymphocyte count (ALC) and interferon‐γ‐producing CD4 + and CD8 + T cells at diagnosis and at viral clearance by an intracellular cytokine assay after stimulating with HAdV whole lysate, hexon, and penton proteins. HAdV infection was defined as the presence of HAdV DNA load in plasma or clinical specimens measured by the polymerase chain reaction assay. Results: Eighteen adult KT recipients were diagnosed with HAdV infection at a median of 16 months (interquartile range [IQR], 2‐39) after KT. The majority (94%) had HAdV‐associated hemorrhagic cystitis. The median ALC at viral clearance was significantly higher compared with diagnosis (2257 cells/mm 3 [IQR, 1544‐3078] vs 1001 cells/mm 3 [IQR, 641‐1385]; P < 0.001). Eleven patients underwent measurement of the HAdV‐specific T‐cell response. The median numbers of CD4 + and CD8 + T cells at viral clearance were significantly higher compared with diagnosis (448 cells/mm 3 [IQR, 248‐651] vs 215 cells/mm 3 [IQR, 159‐272], P = 0.02; and 623 cells/mm 3 [IQR, 242‐772] vs 235 cells/mm 3 [IQR, 129‐266], P < 0.01), respectively. The median percentages of penton‐specific CD4 + and hexon‐specific CD8 + T cells at viral clearance were significantly higher compared with diagnosis (0.012% vs 0%, P = 0.03%; and 0.136% vs 0.016%, P = 0.003, respectively). Conclusions: Our findings suggest a trend of ALC and HAdV‐specific T‐cell immune restoration in KT recipients who achieve successful HAdV clearance.